Recognizing individuality to develop clowning skills.Interview with Lucía Snitcofsky, aka "Lucy Sni" (Itinerarios Educativos, 2025)
This interview seeks to elucidate Lucía Snitcofsky’s distinctive approach to supporting training processes in the field of theater, with a particular emphasis on the clown genre. With a background as both a social worker and a theater educator, Snitcofsky offers her own perspective on artistic development. She states that «an artist is someone who speaks the language» and emphasizes that «she teaches the language so that the learner can decide what they want to say». The interview explores the competencies her students are expected to acquire, the challenges encountered during training, and her own evolving process as an educator. Snitcofsky describes her pedagogical philosophy as a «Tetris of other pedagogies». Central to her approach is the notion of «sharing the threads» that guide her work—fostering a supportive environment rooted in the recognition of others rather than in successes or mistakes, and grounded in trust in each individual’s uniqueness. Her insights contribute to broader reflections on training methodologies, offering valuable implications for general teaching practices as well as for the preparation of trainers.
Keywords: Training; pedagogy; creativity; acknowledgement